Enhancing Elementary Students’ Mathematics Achievement through CTL and Musi Board Media: A Quasi-Experimental Study - Rudi Susanto; Edi Harapan; Mery Novianti (Sustainable, 2026)
This study aims to examine the effect of Contextual Teaching and Learning (CTL) combined with Musi Board media on fourth-grade students’ mathematics achievement. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The sample consisted of two groups: an experimental group taught using the CTL model with Musi Board media and a control group taught using conventional methods with Musi Board media. Data were collected through a mathematics achievement test administered as a pre-test and post-test. The data were analyzed using descriptive and inferential statistics, including normality, homogeneity, and an independent samples t-test. The results showed that students in the experimental group demonstrated a significant improvement in learning outcomes, with the mean score increasing from 49.8 (pre-test) to 72.5 (post-test), compared to the control group, which improved from 49.5 to 65. The t-test analysis indicated a significant difference between the two groups (p < 0.05), confirming the effectiveness of the CTL model. The findings suggest that integrating contextual learning with instructional media enhances students’ engagement, conceptual understanding, and overall mathematics achievement. Therefore, CTL combined with Musi Board media can be considered an effective instructional strategy in elementary mathematics education.